EKSPLORASI POTENSI OLAHAN NANGKA DALAM MENDUKUNG PARIWISATA KULINER DESA PAGELARAN KABUPATEN MALANG - Mariana, Rina Rifqie; Gunawan, Aditia Gustiana; Umam, Nada Itorul; Wibowotomo, Budi; Rohajatien, Ummi (GANESHA: Jurnal Pengabdian Masyarakat, 2025)
This community service activity is a continuation of the 2023 program, which focused on empowering sugarcane sap processing. This year, the activities were expanded to empower the potential of jackfruit in Pagelaran Village, where the fruit, its straw, and seeds have not been fully utilized. The training was conducted by three lecturers and a culinary arts student on September 19, 2024, involving 28 participants from SMEs and farmers, along with three village officials. The material included the production of processed products such as young jackfruit floss, jackfruit seed strudel, jackfruit seed mochi cake, and jackfruit straw dodol. Additionally, branding and digital marketing training through social media and marketplace platforms were provided. This program aims to increase the market value of local products and support the village’s culinary tourism. Participants expressed positive feedback for this initiative